Group portrait at backyard event - Sahl, Ted (photographer):::Creator::::::::::::
Group portrait of people attending the annual Johnie Santucci (not shown) birthday bash in his home. The group is positioned around a woman seated in a chair. Lou Lou is squatting down to the left of the woman's chair, Joey Colyer is in the back row, third from the right, David Treadwell is the first seated man on the right in the next to the last row, Jim Cassara is the first person seated on the right, Frank O'Reilly is the first man on the right, standing in the back row, and Ken Yeager is the sitting with his legs stretched out on the left side.